2017
DOI: 10.1590/1678-7757-2016-0358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound streaming on the disinfection of flattened root canals prepared by rotary and reciprocating systems

Abstract: New technical and scientific developments have been advocated to promote the success of the endodontic treatment. In addition to rotary and reciprocating systems, irrigating solution agitation has been suggested and passive ultrasonic irrigation (PUI) is the most used. Objective: To evaluate, in vitro, the effect of ultrasound streaming (US) in the disinfection of flattened root canal systems prepared by the ProTaper, BioRaCe and Reciproc systems, utilizing the microbiological culture. Methodology: Extracted h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
0
20
0
6
Order By: Relevance
“…A recent study demonstrated the ability of ultrasonic irrigation to reduce significantly the bacterial load in flattened canals instrumented with a reciprocating file (Vasconcelos et al . ). In the same study, the number of microbial colonies present in canals instrumented by a single file was greater than that in canals instrumented with a multi‐file system, clearly indicating the need for complementary irrigation approaches to enhance the disinfection of canals instrumented by single files.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study demonstrated the ability of ultrasonic irrigation to reduce significantly the bacterial load in flattened canals instrumented with a reciprocating file (Vasconcelos et al . ). In the same study, the number of microbial colonies present in canals instrumented by a single file was greater than that in canals instrumented with a multi‐file system, clearly indicating the need for complementary irrigation approaches to enhance the disinfection of canals instrumented by single files.…”
Section: Discussionmentioning
confidence: 97%
“…It is important to highlight the findings relating to the capability of ultrasonic irrigation to improve the quality of pulp tissue debridement in root canals instrumented using a single reciprocating file especially in canals with more challenging anatomy such as an oval shape. A recent study demonstrated the ability of ultrasonic irrigation to reduce significantly the bacterial load in flattened canals instrumented with a reciprocating file (Vasconcelos et al 2017). In the same study, the number of microbial colonies present in canals instrumented by a single file was greater than that in canals instrumented with a multi-file system, clearly indicating the need for complementary irrigation approaches to enhance the disinfection of canals instrumented by single files.…”
Section: Discussionmentioning
confidence: 99%
“…Next, three ultrasonic baths were performed with 1% NaOCl, 17% ethylenediaminetetraacetic acid (EDTA), and phosphate-buffered saline (PBS) solution, respectively, for 10 min each, followed by distilled water to eliminate EDTA and NaOCl residues and open up the dentinal tubules according to a previously described protocol. 6,13 The specimens were sterilized individually in microtubes with distilled water in an autoclave (Cristófoli, Campo Mourão, Brazil) at 121°C for 24 min, inserted in Brain Heart Infusion (BHI) sterile culture media (Difco, Detroit, USA), and submitted to an ultrasonic bath for 10 min for maximum penetration of the culture broth into the dentinal tubules.…”
Section: Specimen Selectionmentioning
confidence: 99%
“…4 Conventional syringe irrigation (CSI) has been routinely used; nevertheless, there are several limitations related to this technique. 5 Aiming for better antisepsis of the root canal system, agitation of the irrigation solution was performed by passive ultrasonic irrigation (PUI), wherein an activation of an ultrasonic tip inside the root canal along the working length (WL) is performed and moved passively in up-and-down motions, 6 helping to remove debris and remnants of the pulp tissue. 6,7 However, further studies must be carried out to fully clarify the issue of debris extrusion performed by PUI activation.…”
Section: Introductionmentioning
confidence: 99%
“…Porém, esse fenômeno pode ser influenciado por diversos fatores dentro do canal radicular: os pequenos volumes de irrigante (van der Sluis et al, 2007, Macedo et al, 2014a; o tempo de agitação ultrassônica (Macedo et al, 2014b); a potência do equipamento de ultrassom (Chen et al, 2013); o contato da solução ativada com o ar atmosférico (Chen et al, 2013;Macedo et al, 2014a); o tipo de instrumento ativado (van der Sluis et al, 2007;Chen et al, 2013;Macedo et al, 2014a,b); a anatomia do canal radicular (Castelo-Baz et al, 2012;Vasconcelos et al, 2017), e as regiões de istmos (Thomas et al, 2014 (Paiva et al, 2012(Paiva et al, , 2013Nakamura et al, 2018 (Harrison et al, 2010;Cachovan et al, 2013). A PUI apresentou os melhores níveis de desinfecção em dentes contaminados com Enterococcus faecalis em canais com anatomia transversal ovalada (Vasconcelos et al, 2017). Estudo in vitro, comparando a efetividade antimicrobiana da PUI com sistema de irrigação por pressão negativa, mostrou que a PUI foi mais efetiva na desinfecção de canais simulados do que o sistema EndoVac (Townsend et al 2009).…”
Section: Discussão Dos Resultadosunclassified